TABLIGH, SIDDIQ, AMANAH, FATHONAH: MENGGALI SIFAT RASUL UNTUK KARAKTER IDEAL SISWA - Fitri , Salsabila; Ana Bakri, Saidatul; Akustika Romansa, Ariel; Gusmaneli, Gusmaneli (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This article extract the character of an apostle, in a religious context, reflects the character of divine messengers sent to guide humanity. This article explores the qualities of apostles that are generally recognized and emulated in student character education. Rasulullah, may Allah SWT bless him and grant him peace. Al Anbiya’s verse 107 and Al Ahzab verse 21. Those attributes include Siddiq, Amanah, Tabligh and Fathonah. Prophets who are endowed with courage to face challenges and uphold the truth, as well as patience in the face of obstacles. Outstanding communication skills and wise leaders are other qualities that complement their role as messengers of God. From these attributes of the Prophet we can teach it as a provision for running life in the future. In this abstract, we see how an understanding of these attributes can become an ideal character mastery for a pupil or student.